Revenge of the angels - Ziegler, Jennifer, 1967- (Scholastic Press, 2015)
The eleven-year-old Brewster triplets, Dawn, Darby, and Delaney, are afraid this is going to be the worst Christmas ever--they have been cast as angels in their local Christmas pageant just because they are girls, their mother, older sister, and aunt are stuck in Boston because of the snow, someone is stealing outdoor Christmas decorations and baked goods, and their father is just too busy for Christmas.